Early transient radiation-induced brachial plexopathy in locally advanced head and neck cancer - Metcalfe, Evrim; Etiz, Durmus (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study : Early transient brachial plexopathy following radiotherapy (RT) in patients with head and neck cancer may be underreported and associated with a dose-response. Our purpose was to determine the incidence of early transient radiation-ınduced brachial plexopathy (RIBP) in patients receiving primary RT (± chemotherapy) for locally advanced head and neck cancer (HNC). Material and methods: Twenty-seven locally advanced HNC patients who have no finding of brachial plexopathy at the diagnosis were evaluated 3 times by a specifically developed 13-item questionnaire for determining early transient RIBP. The 54 brachial plexus in 27 patients were delineated and dose volume histograms were calculated. Results : Median follow-up period was 28 (range: 15–40) months. The mean BP volume was 7.9 ±3.6 cm 3 , and the mean and maximum doses to the BP were 45.3 (range: 32.3–59.3) Gy, and 59.4 (range: 41.4–70.3) Gy, respectively. Maximum dose to the BP was ≥ 70 Gy only in 2 nasopharyngeal cancer patients. Two (7%) early transient RIBP were reported at 7th and 8th month after RT under maximum 67.17 and 55.37 Gy, and mean 52.95 and 38.60 Gy RT doses. Conclusion : Two (7%) early RIBP were seen in the patient group, although brachial plexus maximum doses were ≥ 66 Gy in 75% of patients.